2019
DOI: 10.1103/physrevapplied.12.024039
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Efficiencies and Performance-Limiting Factors of Inorganic and Hybrid Perovskite Solar Cells

Abstract: The Shockley and Queisser limit, a well-known efficiency limit for a solar cell, is based on unrealistic physical assumptions and its maximum limit is seriously overestimated.To understand the power loss mechanisms of record-efficiency cells, a more rigorous approach is necessary. Here, we have established a formalism that can accurately predict absolute performance limits of solar cells in conventional thin film form. In particular, a formulation for a strict evaluation of the saturation current in a nonblack… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…4. With increment of the thickness of p-GaAsN the absorption of light increases which are reported in the earlier studies [8,[31][32][33].…”
Section: Impact Of Thickness On the Quantum Efficiencysupporting
confidence: 63%
“…4. With increment of the thickness of p-GaAsN the absorption of light increases which are reported in the earlier studies [8,[31][32][33].…”
Section: Impact Of Thickness On the Quantum Efficiencysupporting
confidence: 63%
“…(The designed cell can theoretically reach an efficiency limit of 33% and the theoretical conversion limit of stacked cells is 43%.) 24,25 Although the perovskite battery has a high energy-saving limit, simple process, rapid development, and impressive performance in the laboratory, there is still a long way to go for large-scale practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, there are a considerable number of studies that assess features beyond the SQ model, considering absorber and architecture key criteria. [76][77][78][79][80] As an example, Rau and Kirchartz conceptually demonstrated that for real cells' absorbance, a Gaussian distribution function should be used to describe the absorption edge, instead of an ideal step function. [80] Notwithstanding, the SQ model is still widely used to evaluate solar cell performance, as its abstraction level allows for a fair crosslink between technologies.…”
Section: Demand For Light Managementmentioning
confidence: 99%